Sistim Kekerabatan sebagai Katalisator Peran Ulama Keturunan Arab di Jakarta - Yasmine Zaki Shahab (Antropologi Indonesia, 2005)
Literature on the history of Islam in Indonesia notes the tremendous role of the Arabs who migrated to Indonesia from Hadramaut (South Yaman) for many centuries. Introduction of Islam through noble people has brought the Arabs both into prestigious status as well as to the Indonesian struggle against the Dutch colonialism. This historical background has continued, but in the last decades there has been a shift in their religious role contributed by various factors, both internal and external factors. This writing focuses only on the internal factor, namely the kinship system which is under rapid changes amongst the Arabs. Based on both research and experience, the author clarifies the relationship between the kinship system and social change in the religious sphere among Arab community in Jakarta. Key words: Arab kinship; Islam; social stratification; voluntary organization.